Molecular analysis of zoonotic pathogens in free-ranging six-banded armadillos (Euphractus sexcinctus) from the Brazilian semiarid region - Ilanna Vanessa Pristo de Medeiros Oliveira; José Artur Brilhante Bezerra; Gabriela Hémylin Ferreira Moura; Ana Carolina Yamakawa; Mariana Guimarães Nilsson; Jéssica da Silva Ferreira; Amanda Haisi; Felipe Fornazari; Hélio Langoni; João Marcelo Azevedo de Paula Antunes (Revista Brasileira de Parasitologia Veterinária)
Abstract This study investigated infection by Leishmania spp., Leptospira spp., Toxoplasma gondii, and Trypanosoma cruzi in six-banded armadillos (Euphractus sexcinctus) from the semiarid region of northeastern Brazil. Twenty specimens of E. sexcinctus were captured alive by wildlife veterinarians from their natural habitats in different locations. The animals were euthanized following induction of anesthesia, and different biological samples were collected. Infection with four pathogens was subsequently evaluated: Leishmania infection was investigated by spleen and liver Polymerase Chain Reaction (PCR); Leptospira spp. infection was evaluated by kidney PCR and serologically by microscopic agglutination test; T. gondii infection was assessed by PCR of the heart, lung, and spleen; and T. cruzi infection was investigated by heart and whole blood PCR and hemoculture. All tests presented negative results apart from whole blood PCR to detect T. cruzi, which was positive in one of the 20 animals tested and confirmed by genetic sequencing. It is important to highlight that this is the first study comprising a molecular investigation of different zoonotic pathogens in six-banded armadillos, and the findings reported here bring new and important knowledge regarding zoonotic diseases in this species.